Multi-switch scanning keyboards: A theoretical study of simultaneous parallel scans with QWERTY layout - Sandnes, Frode Eika; Eika, Evelyn; Medola, Fausto Orsi [UNESP] (Springer Nature, 2018)
Scanning keyboards can be useful aids for individuals with reduced motor function. However, scanning input techniques are known for being very slow to use because they require waiting for the right cell to be highlighted during each character input cycle. This study explores the idea of parallel scanning keyboards controlled with multiple switches and their theoretical effects on performance. The designs explored assume that the keyboard layouts are familiar to users and that the mapping between the switches and the keyboards are natural and direct. The results show that the theoretical performance increases linearly with the number of switches used. Future work should perform user tests with parallel scans to assess the practicality of this approach.
Keywords: Joystick; Parallel scans; Reduced motor function; Scanning keyboards; Text entry